Sistem Informasi Manajemen Menggunakan Database Karyawan Dalam Melakukan Perhitungan Penggajian Pada Percetakan UD Wahyu - Aidhawani Aidhawani; Muhammad Irwan Padli Nasution (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
Human resources play an important role in helping an organization or company achieve its goals, and as a result, business growth is highly dependent on employee performance. Each employee receives a salary directly from the company, which is distributed at a time determined by the company, in accordance with the terms of the employee agreement with the company. UD Wahyu Printing is still doing it. At the UD Wahyu printing press, payroll calculation activities are still carried out manually using a calculator and manual recording which causes errors in calculating an employee's salary, so an electronic system must be created to overcome this problem. As for a goal to be achieved in this research is to perform a salary calculation of employees by implementing an automatic payroll system to make it more effective and efficient. This study uses a type of qualitative research with interviews and direct observation methods. The results of this study through the stages of implementation and trials carried out that the employee payroll information system at the UD Wahyu printing press can link payroll information with employee attendance procedures, and the data is stored in a database so that reports can be printed. And the system can provide facilities to employees regarding payroll calculations.